Hierarchical structures of transition metal cyanide coordination compounds

By controlling the hierarchical structure and physical characteristics of TMCCC materials, the performance degradation of electrochemical batteries at high discharge rates is solved, and the high efficiency and long life of the batteries are achieved.

JP2025511191APending Publication Date: 2025-04-15NATRON ENERGY INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024558030
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-05
Filing Date
2022-12-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In existing electrochemical batteries, the characteristics of transfer metal blue compound (TMCCC) materials, such as surface area and density, cannot be effectively controlled, resulting in the decline in the performance of electrochemical batteries at high discharge rates, especially the impact of charge and discharge capacity and battery life.

Method used

Using a hierarchical structure of TMCCC materials, the performance of electrochemical cells is optimized by controlling the size of their primary crystals and the size range of weak aggregates to ensure the specific surface area, density and particle size distribution of the material.

Benefits of technology

By optimizing the physical characteristics of TMCCC materials, it is possible to maintain the high efficiency of the battery at high discharge rates, ensure that the battery charge and discharge capacity exceeds 70% of the nominal capacity, and extend the battery service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511191000001_ABST
    Figure 2025511191000001_ABST
Patent Text Reader

Abstract

Systems and methods of implementation and manufacture of hierarchical systems for use with TMCCC-containing conductive structures (e.g., electrodes), and methods of using and manufacturing such structures and electrochemical cells containing these devices. x M y N z Ti a1 V a2 Cr a3 Mn a4 Fe a5 Co a6 Ni a7 Cu a8 Zinc a9 Ca a10 Mg a11 [R(CN)6] b (H2O) c The method includes combining electrochemically active materials to produce a hierarchical structure, the hierarchical structure having a plurality of primary crystallites having a size D1, the plurality of primary crystallites being aggregated into a collection of agglomerates, each agglomerate having a size D2>D1, a4>0, and either a5=0 or a5>0.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to application Ser. No. 18 / 061,871, filed in the United States on December 5, 2022. Application Ser. No. 18 / 061,871 claims priority to application Ser. No. 18 / 051,765, filed in the United States on November 1, 2022. Application Ser. No. 18 / 061,871 claims priority to application Ser. No. 17 / 711,623, filed in the United States on April 1, 2022. This application claims priority to application Ser. No. 18 / 051,765, filed in the United States on November 1, 2022. Application Ser. No. 18 / 051,765 claims priority to application Ser. No. 17 / 711,623, filed in the United States on April 1, 2022. This application claims priority to application Ser. No. 17 / 711,623, filed in the United States on April 1, 2022.

[0002] The present invention relates generally to electrochemical cells that include electrochemically active coordination compounds in one or more conductive structures within the electrochemical cell, and more specifically, but not exclusively, to improvements in electrochemical cells having, for example, transition metal cyanide coordination compound (TMCCC)-containing conductive structures, such as a new class of transition metal cyanide coordination compounds (TMCCC) for use in electrodes, as well as electrochemical cells made using such TMCCC-containing conductive structures. [Background technology]

[0003] The subject matter discussed in the Background section should not be considered to be prior art merely as a result of its mention in the Background section. Similarly, the problems mentioned in the Background section or related to the subject matter of the Background section should not be considered to have been previously recognized in the prior art. The subject matter of the Background section merely represents different approaches that may be inventive in their own right.

[0004] Electrochemical cells play an important role in energy storage in a variety of applications, including but not limited to electric vehicles, grid storage applications, data center infrastructure, and consumer electronics. Important properties of electrochemical cells include their ability to store, hold, and release charge as needed. Applications of electrochemical cells are influenced by the discharge rate at which the cell can be emptied without significant capacity loss, as well as any changes in the operating characteristics of the cell due to the accumulation, storage, and release of charge.

[0005] Figure 1 shows a Nyquist plot highlighting the metrics used to quantify an electrochemical cell. The Nyquist plot in Figure 1 was generated by electrochemical impedance spectroscopy (EIS) of a cell, revealing the inner workings of the plotted cell. The plot contains a semicircle, and the value of the intersection of the semicircle with the real axis (A) is known as the equivalent series resistance (ESR) and is a measure of the battery's internal resistance. The width of the semicircle (B) indicates the charge transfer resistance of the electrochemical cell. A larger semicircle width is detrimental to the performance of the electrochemical cell in that the power output of the cell is greatly compromised. The 45° slope (C) indicates ion diffusion through the electrochemical cell.

[0006] Li-ion batteries have become a popular battery architecture for mobile applications such as electric vehicles and portable electronic devices due to the ability of Li-ion battery clusters to deliver high energy density without sacrificing performance and lifespan. However, the increasing cost of lithium as well as other essential components of Li-ion batteries is spurring the selection of alternative, cheaper options for applications where high energy density is not required.

[0007] Sodium is much more abundant than lithium. In similar applications, and to the extent that sodium-ion batteries offer competitive performance compared to Li-ion batteries, sodium-ion architectures can serve as suitable substitutes for lithium, given the appropriate surrounding framework. Transition metal cyanide coordination compounds (TMCCCs) can be synthesized to create open frameworks that allow high mobility of sodium ions through the lattice.

[0008] The composition of TMCCC has been described for use in cathode electrodes, but little attention has been paid to the morphology of the material. For example, REF[1] reports that A x They describe the use of a cathode comprising TMCCC having the form M1M2(CN)6, where the A cation can be Na or K, x=0-2, and each of M1 and M2 is a metal cation such as Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ca, Mg, etc., but do not specify the physical properties of the material.

[0009] The lack of enforceable physical criteria opens the possibility of creating TMCCC materials that meet all the desired / required compositional criteria, but still perform poorly when actually used in electrochemical cells.

[0010] The first important property is the specific surface area of ​​TMCCC, measured by nitrogen adsorption and calculated using the Brunauer-Emmett-Teller (BET) theory, which is primarily correlated with the primary particle size of TMCCC. As a secondary effect, the BET decreases with additional aggregation, revealing the pores in the material as well as the spacing between the strong aggregates. Figure 2 shows the specific surface area of ​​the TMCCCs cited in Examples III, IV, VII, and VIII described herein, as well as the semicircular width of the electrochemical cells made with these TMCCCs. As can be seen from Figure 2, when the specific surface area of ​​the TMCCCs falls below a certain point, the semicircular width of the electrochemical cells made with the TMCCCs increases significantly. One common theory is that the low specific surface area may correspond to the closure of internal pores and blocking of ion transfer, thus significantly increasing the charge transfer resistance. The observed large increase in semicircular width as a result of the reduction in TMCCC specific surface area highlights the opportunity to impose boundaries on the specific surface area of ​​TMCCC to ensure good performance of electrochemical cells.

[0011] The tap density of TMCCC helps to reveal the closeness of the agglomerates and the voids between them. Figure 3 shows the tap density of the TMCCCs cited in the examples described herein, including Examples III, IV, VI, and VII, as well as the semicircular width of the electrochemical cells made with those TMCCCs. As can be seen from Figure 3, when the tap density of a TMCCC exceeds a certain point, the semicircular width of the electrochemical cells made with that TMCCC increases significantly. This increase in semicircular width as a result of the reduction in TMCCC surface area highlights the opportunity to impose a boundary on the tap density to ensure a well-performing electrochemical cell.

[0012] The median diameter of the agglomerates, measured by a particle size analyzer (PSA) and recorded as D50, is also preferably considered and carefully selected. TMCCCs with agglomerate D50 outside the desired range may result in electrodes with mechanical defects such as cracks or uneven coating. Similarly, the 10th percentile (D10) and 90th percentile (D90) values ​​must also be limited to the desired range.

[0013] Controlling these physical TMCCC properties, including tap density, surface area, and one or more of D10, D50, and / or D90, can be important to understanding whether a subsequent electrochemical cell will function properly and maintain its specific capacity even when discharged at rates higher than the nominal rate.

[0014] There would be advantages to a properly implemented hierarchical system for use with TMCCC-containing conductive structures (e.g., electrodes), as well as methods of use and manufacture of such structures and electrochemical cells containing these devices. Summary of the Invention

[0015] Systems and methods of implementation and manufacture of hierarchical systems for use with TMCCC-containing conductive structures (e.g., electrodes), as well as methods of using and manufacturing such structures and electrochemical cells that include these devices, are disclosed. The following Summary of the Invention is provided to facilitate understanding of some technical features related to electrodes that include TMCCC materials (and their methods of manufacture) and is not intended to be a complete description of the invention. A complete understanding of the various aspects of the invention can be obtained by reviewing the entire specification, claims, drawings, and abstract as a whole. In addition to TMCCC materials, the invention is applicable to other electrochemically active compounds, such as other coordination materials, and other conductive structures that include coordination materials.

[0016] The embodiment is L x M y N z Ti a1 V a2 Cr a3 Mn a4 Fe a5 Co a6 Ni a7 Cu a8 Zinc a9 Ca a10 Mg a11 [R(CN)6] b (H2O) cIt may include a novel class of TMCCCs having a coordination complex with a synthesized composition, the composition includes a plurality of particles, the plurality of particles include a hierarchical structure, the hierarchical structure includes a plurality of primary crystallites having a size of D1, and the plurality of primary crystallites aggregate into an aggregate of weak aggregates (each weak aggregate has a size D2>D1). One or more of the following may apply: (a) Each of L, M, and N represents an alkali metal, (b) 0≦x≦2, (c) 0≦y≦x, (d) 0≦z≦x, (e) 0<b≦1, (f) 0<c, (g) For each element of the set {a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11}, 0≦{a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11}≦1, (h) At least one of {a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11} is >0, a4>0, and both a4 and a5 are >0.

[0017] Embodiments of the electrode can include one or more conductive carbons, one or more polymer binders, a current collector, and one or more TMCCCs, (a) the conductive carbon includes nanoparticle carbon, (b) the current collector includes a metal foil, (c) the metal foil includes a surface coating containing carbon, (d) the polymer binder includes a functionalized SEBS binder, (e) the TMCCC can include the composition specified herein.

[0018] Embodiments of the electrochemical cell can include a cell stack having a liquid electrolyte, an anode electrode, a separator, and a cathode electrode, the electrodes are in electrochemical communication with the liquid electrolyte, (a) the cell stack may contain additional anodes, cathodes, or reference electrodes, (b) the liquid electrolyte includes a polar organic solvent combined with an alkali metal salt, (c) the separator includes a polymer membrane, (d) the membrane may have a surface coating containing nanoparticle alumina and boehmite, (e) the anode electrode includes a TMCCC, (f) the anode electrode includes a conductive carbon, (g) the cathode electrode includes a TMCCC having the composition described herein.

[0019] Embodiments of the present invention alternatively may include a coordination complex represented by M a N b P x Q y [R(CN)6] z and may further include a plurality of particles, the particles including a hierarchical structure, the hierarchical structure including a plurality of primary crystallites having a size D1, the primary crystallites aggregating into larger weak aggregates having a size D2. Further, one or more of the following are applicable: (a) each of M and N represents an alkali metal, (b) each of P, Q, and R is a metal cation such as Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ca, Mg, etc., (c) 0 < a ≦ 2, (d) 0 ≦ b ≦ a and 0 ≦ x ≦ 1, (e) 0 ≦ y ≦ 1, (f) at least one of x and y is greater than 0, (g) 0 < z ≦ 1, (h) D1 < 1 μm, (i) D2 includes a particle size distribution with a 50th percentile size greater than 6 μm, (j) the 10th percentile size of D2 is greater than 1.5 μm, (k) the 90th percentile size of D2 is greater than 7.5 μm, (l) the TMCCC material has a specific surface area of > 2 m 2 per gram, (m) the TMCCC material has a tap density of < 0.9 g / cm 3 .

[0020]

[0013] An embodiment of the invention may include a cell stack having a liquid electrolyte, an anode electrode, a separator, and a cathode electrode, the electrodes being in electrochemical communication with the liquid electrolyte, the liquid electrolyte comprising a polar organic solvent in combination with an alkali metal salt, the liquid electrolyte comprising one or more nitriles (e.g., one or more of acetonitrile or succinonitrile), the liquid electrolyte comprising one or more cyclic carbonates (e.g., the cyclic carbonates include one or more of ethylene carbonate and propylene carbonate) and one or more olefins (e.g., one or more of ethylene carbonate and propylene carbonate). the liquid electrolyte comprises an additive; the separator comprises one or more polymeric membranes, one or more of which may comprise a surface coating comprising nanoparticle alumina and boehmite; the anode electrode comprises TMCCC, a conductive carbon, a metal structure, and a carbonaceous intercalation material; the cathode electrode comprises TMCCC, the TMCCC being L x M y N z Ti a1 V a2 Cr a3 Mn a4 Fe a5 Co a6 Ni a7 Cu a8 Zinc a9 Ca a10 Mg a11 [R(CN)6] b (H2O) cA composition and a plurality of particles of the composition, the plurality of particles including a hierarchical structure, the hierarchical structure including a plurality of primary crystallites having a size of D1, the plurality of primary crystallites being aggregated into an aggregate of weak aggregates, the size D2 of each weak aggregate being > D1, each of L, M, and N represents an alkali metal, R represents a transition metal, 0 ≦ x ≦ 2, 0 ≦ y ≦ x, 0 ≦ z ≦ x, 0 < b ≦ 1, 0 < c, for each element of the set {a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11}, 0 ≦ {a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11} ≦ 1, at least one of {a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11} is > 0, a4 > 0, 0.25 μm < D1 < 1 μm, and optionally a5 > 0 as well.

[0021] Embodiments can include a hybrid capacitor including a cell stack having a liquid electrolyte, a capacitive electrode, a separator, and a cathode electrode, the electrodes being in electrochemical communication with the liquid electrolyte, the liquid electrolyte including a polar organic solvent combined with an alkali metal salt, the liquid electrolyte including one or more nitriles (e.g., the nitrile includes acetonitrile and / or succinonitrile), the liquid electrolyte including a combination of one or more cyclic carbonates and one or more linear carbonates (e.g., the cyclic carbonate includes ethylene carbonate and / or propylene carbonate, and the linear carbonate includes dimethyl carbonate, diethyl carbonate, and / or ethyl methyl carbonate), the liquid electrolyte including one or more additives, the separator including a polymer membrane, one or more of which can include a surface coating including nanoparticle alumina and boehmite, the capacitive electrode including conductive carbon, the cathode electrode including TMCCC, and TMCCC is L x M y N z Ti a1 V a2 Cr a3 Mn a4 Fe a5 Co a6 Nia7 Cu a8 Zn a9 Ca a10 Mg a11 [R(CN)6] b (H2O) c comprises a composition and a plurality of particles of the composition, the plurality of particles comprising a hierarchical structure, the hierarchical structure comprising a plurality of primary crystallites having a size of D1, the plurality of primary crystallites being aggregated into an aggregate of weak aggregates, the size D2 of each weak aggregate being > D1, each of L, M and N represents an alkali metal, R represents a transition metal, 0 ≦ x ≦ 2, 0 ≦ y ≦ x, 0 ≦ z ≦ x, 0 < b ≦ 1, 0 < c, for each element of the set {a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11}, 0 ≦ {a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11} ≦ 1, at least one of {a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11} is > 0, a4 > 0, 0.25 μm < D1 < 1 μm, and optionally a5 > 0.

[0022] Any of the embodiments described herein can be used alone or together in any combination with each other. The inventions encompassed herein can also include embodiments that are only partially mentioned or implied, or not mentioned or implied at all, in the summary or abstract of this invention. The various embodiments of the present invention may be motivated by various deficiencies of the prior art that may be discussed or implied at one or more places in this specification, but the embodiments of the present invention do not necessarily address any of these deficiencies. In other words, different embodiments of the present invention may address different deficiencies that may be discussed herein. Some embodiments may only partially address some or only one of the deficiencies that may be discussed herein, and some embodiments may not be able to address any of these deficiencies.

[0023] Other features, benefits, and advantages of the present invention will become apparent by reviewing this disclosure, including the specification, drawings, and claims. [Brief description of the drawings]

[0024] The accompanying drawings further illustrate the present invention and, together with the detailed description of the invention, serve to explain the principles of the invention, in which like reference numbers indicate identical or functionally similar elements throughout the different drawings, and are incorporated in and form a part of this specification.

[0025] [Figure 1] 1 shows a Nyquist plot highlighting metrics used in quantifying the performance of an electrochemical cell.

[0026] [Diagram 2] 1 shows the specific surface areas of the TMCCCs cited in Examples II, V, VI, and VIII described herein, as well as the semicircular widths of electrochemical cells made with these TMCCCs.

[0027] [Diagram 3] 1 shows the tap densities of the TMCCCs cited in the examples described herein, including Examples III, IV, VII, and VIII, as well as the semicircular widths of electrochemical cells made with these TMCCCs.

[0028] [Figure 4] 1 shows a collection of discharge curves of the electrochemical cell of Example I at 1C, 5C, 10C and 20C.

[0029] [Diagram 5] 1 shows a collection of discharge curves of the electrochemical cell of Example II at 1C, 5C, 10C and 20C.

[0030] [Figure 6] 1 shows a collection of discharge curves of the electrochemical cell of Example III at 1C, 5C, 10C and 20C.

[0031] [Figure 7]FIG. 13 shows the subsequent assembly of electrodes made with TMCCC of Example X with no apparent surface defects.

[0032] [Figure 8] FIG. 1 shows the resultant coat made using TMCCC of Example XI.

[0033] [Figure 9] 13 shows charge-discharge cycling of the electrochemical cell prepared in Example XII, confirming that a functional electrochemical cell can be prepared by pairing a TMCCC cathode electrode with a PBA anode.

[0034] [Figure 10] 13 shows a collection of charge / discharge curves of the electrochemical cell prepared in Example XIII at C / 5, demonstrating that a functional electrochemical cell can be prepared by pairing a TMCCC cathode with a hard carbon anode.

[0035] [Figure 11] FIG. 1 shows the hierarchical structure of the TMCCC of the present disclosure in contrast to the nanoparticle TMCCC described in REF[2].

[0036] [Figure 12] 13 shows a collection of charge / discharge curves at C / 5 for electrochemical cells made with the material of Example XIV.

[0037] [Figure 13] 1 shows a typical electrochemical cell. Detailed Description of the Invention

[0038] Embodiments of the present invention provide systems and methods of implementation and manufacture of hierarchical systems for use with TMCCC-containing conductive structures (e.g., electrodes), and methods of using and manufacturing such structures and electrochemical cells containing these devices. The following description is presented to enable one of ordinary skill in the art to make and use the invention and is provided in the context of a patent application and its requirements.

[0039] Various modifications to the preferred embodiments and generic principles and features described herein will be readily apparent to those skilled in the art, and thus the present invention is not intended to be limited to the embodiments shown, but is to be accorded the widest scope consistent with the principles and features described herein.

[0040] definition

[0041] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art to which this general inventive concept belongs. Terms as defined in commonly used dictionaries should be interpreted to have a meaning consistent with their meaning in the context of the relevant art and this disclosure, and will not be interpreted in an idealized or overly formal sense unless expressly so defined herein.

[0042] The following definitions apply to some of the aspects described with respect to specific embodiments of the invention. These definitions may be expanded upon herein as well.

[0043] As used herein, the term "or" includes "and / or," which includes any and all combinations of one or more of the associated listed items. Phrases such as "at least one of," when preceding a list of elements, modify the entire list of elements and not individual elements of the list.

[0044] As used herein, the singular terms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, a reference to an object can include a plurality of objects unless the context clearly dictates otherwise.

[0045] Also, as used in the description herein and throughout the claims which follow, the meaning of "in" includes "in" and "on," unless the context clearly dictates otherwise. When an element is referred to as being "on" another element, it will be understood that it may be directly on the other element, or there may be intervening elements between them. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements.

[0046] As used herein, the term "collection" refers to a collection of one or more objects. Thus, for example, a collection of objects can include a single object or multiple objects. The objects of the collection can also be referred to as members of the collection. The objects of the collection can be the same or different. In some examples, the objects of the collection can share one or more common characteristics.

[0047] As used herein, the term "adjacent" refers to being near or adjoining. Adjacent objects may be spaced apart from one another or may be in actual or direct contact with one another. In some instances, adjacent objects may be joined to one another or may be integrally formed with one another.

[0048] As used herein, the terms "connect," "connected," and "connecting" refer to a direct coupling or connection. Connected objects are free or substantially free of intermediate objects or collections of objects, as the context indicates.

[0049] As used herein, the terms "couple," "coupled," and "coupling" refer to an operative connection or coupling. Coupled objects may be directly connected to one another or may be indirectly connected to one another, for example through a collection of intermediate objects.

[0050] The use of the term "about" applies to all numerical values, whether or not explicitly stated. The term generally refers to a range of numbers that one of ordinary skill in the art would consider a reasonable deviation from the recited numerical values ​​(i.e., having an equivalent function or result). For example, the term can be interpreted to include deviations of ±10% of the given numerical value, provided that such deviations do not alter the return value or the result of the value. Thus, a value of about 1% can be interpreted as a range of 0.9% to 1.1%.

[0051] As used herein, the terms "substantially" and "substantial" refer to a great degree or extent. When used in connection with an event or circumstance, these terms can refer to instances in which the event or circumstance occurs exactly, as well as instances in which the event or circumstance occurs approximately, for example, taking into account typical tolerance levels or variability of the embodiments described herein.

[0052] As used herein, the terms "optional" and "optionally" mean that the subsequently described event or circumstance may or may not occur, and that the description includes instances in which the event or circumstance occurs and instances in which the event or circumstance does not occur.

[0053] As used herein, the term "size" refers to a characteristic dimension of an object. Thus, for example, the size of an object that is spherical can refer to the diameter of the object. For objects that are non-spherical, the size of the non-spherical object can refer to the diameter of a corresponding spherical object that exhibits or has a particular set of derivable or measurable properties that are substantially the same as those of the non-spherical object. Thus, for example, the size of a non-spherical object can refer to the diameter of a corresponding spherical object that exhibits substantially the same light scattering or other properties as those of the non-spherical object. Alternatively, or in conjunction, the size of a non-spherical object can refer to the average of the object's various orthogonal dimensions. Thus, for example, the size of an object that is a spheroid can refer to the average of the object's major and minor axes. When referring to a collection of objects having a particular size, it is contemplated that the object may have a distribution of sizes around the particular size. Thus, as used herein, the size of a collection of objects can refer to a typical size of a distribution of sizes, such as an average size, a median diameter, or a peak size.

[0054] As used herein, the term "hybrid capacitor" refers to an electrochemical device in which one electrode contains an active material that stores ions in the bulk of the particle by undergoing a faradaic reaction (a reaction that changes oxidation or valence state). Examples include ceramics such as TMCCC, graphite, hard carbon, and oxides and phosphates. That electrode is the "battery electrode." However, the second electrode in the device is only capacitive. This means that there is never a faradaic reaction, although charge may build up on the surface as the electrode is brought to a more extreme electrochemical potential. Combining one faradaic electrode with one capacitive electrode creates a device with desirable properties such as rapid discharge and recharge capability or long cycle life. An electrochemical cell containing two electrodes, one of which contains a TMCCC material, can include an example of a hybrid capacitor. The unique attribute is that one of the electrodes undergoes a non-faradaic charge storage reaction.

[0055] The TMCCC materials described herein can be used in the electrodes of an electrochemical cell. The electrochemical cell may also include additional electrodes, an electrolyte, and a separator membrane. The optional additional electrodes may include a second TMCCC material, a carbon material such as activated carbon, hard carbon, or graphite, or another material. The electrolyte may include one or more organic solvents, such as acetonitrile, cyclic or linear carbonates, or other organic solvents, or water. The separator membrane may include a polymer and may have a surface coating, including, but not limited to, nano alumina and boehmite.

[0056] As used herein, the term "electrode" in the context of an electrochemical cell may have different meanings and may include different component assemblies of an electrochemical cell in different contexts and for different audiences. For example, an electrode composed of TMCCC, carbon, and binder, and a solvent used in the slurry processing to make the electrode, is typically considered to be completely separate from the current collector. This electrode structure can be placed on any number of current collectors with different compositions (aluminum, copper, etc.) or mechanical properties (thickness, surface roughness, etc.). One precise definition would refer to an "electrode" that includes both the two components: the "active layer" or "electrode composite" that includes the TMCCC, carbon, and binder, and, in turn, the current collector, which may have subcomponents such as special surface coatings, or special design features such as physical dimensions. This application adopts a special terminology used herein to avoid some of the imprecision that exists when referring to electrodes of an electrochemical cell. This term is a "conductive structure" and includes electrodes and other electrochemically active structures that may be used as electrodes. Some larger structures, including electrodes, may also be such "conductive structures" within the meaning of this application, unless the context would reasonably suggest otherwise to one of ordinary skill in the art informed by an understanding of this disclosure and the teachings and claims presented herein.

[0057] This disclosure highlights a new class of TMCCC materials with a wide range of specific surface areas, tap densities and median particle sizes. A set of criteria is disclosed that limits the specific surface area, tap density and median particle size to ensure low semicircular width and the ability to access more than 70% of the nominal capacity of an electrochemical cell even when discharged at 20 times the nominal discharge rate.

[0058] The following examples demonstrate the importance of these physical form criteria, which are disclosed as part of the embodiments of the present invention.

[0059] Example I

[0060] Composition Na 1.24 Mn 0.78 Fe 0.22 [Fe(CN)6] 0.88 (H2O) 2.82 , tap density 0.79g / cm 3 , specific surface area 4.23m 2 TMCCC cathode material, with D10, D50, and D90 values ​​of 0.1 μm / g and 5.6 μm, 8.5 μm, and 12.9 μm, respectively, was mixed with an elastomeric adhesive binder and nanoparticle carbon black in an organic solvent blend to form a slurry. This slurry was deposited onto a carbon-coated aluminum foil current collector using a drawdown coater and dried at 60 °C for 35 minutes to evaporate the solvent. The subsequent coat was calendered (roll pressed) to further densify it, vacuum dried, and cut into electrodes for use in electrochemical cells. An electrochemical cell was then assembled by combining the TMCCC electrode, the activated carbon electrode, a porous membrane separator, and an electrolyte containing bis(trifluoromethanesulfonyl)imide sodium (I) salt and acetonitrile solvent. Electrochemical testing of this cell was performed, including electrochemical impedance spectroscopy and galvanostatic charge-discharge cycling, e.g., galvanostatic followed by N discharges (e.g., N=5) at 0.2C, 1C, 5C, 10C, and 20C.

[0061] 4 shows a collection of discharge curves for the electrochemical cell of Example I at 1 C, 5 C, 10 C and 20 C. Even at 20 times the nominal discharge rate, the available capacity is greater than 70% of the nominal capacity (71.5% of the 1 C capacity).

[0062] Example II

[0063] Composition Na 1.18 Mn 0.77 Fe 0.24 [Fe(CN)6] 0.86 (H2O) 2.44 , tap density 0.68g / cm 3 , specific surface area 1.83m 2 The TMCCC cathode, having a Cr content of 1.0 μm / g and D10, D50, and D90 values ​​of 7.7 μm, 12.3 μm, and 18.1 μm, respectively, was processed into an electrode as described in Example I. An electrochemical cell was then fabricated according to the same procedure as in Example I. Electrochemical testing of the cell was performed, including electrochemical impedance spectroscopy and five galvanostatic charge-discharge cycles at a charge rate of 1 C and discharge rates of 0.2 C, 1 C, 5 C, 10 C, and 20 C.

[0064] 5 shows a collection of discharge curves for the electrochemical cell of Example II at 1 C, 5 C, 10 C and 20 C. Unlike the cell of Example I, the cell of Example II only achieves 66% of its nominal capacity when discharged at 20 times the nominal rate.

[0065] Example III:

[0066] Composition Na 1.25 Mn 0.75 Fe 0.25 [Fe(CN)6] 0.89 (H2O) 2.95 , tap density 0.97g / cm 3 , specific surface area 2.22m 2The TMCCC cathode material, having a ZnO / g and D10, D50, and D90 values ​​of 7.3 μm, 10.4 μm, and 14.4 μm, respectively, was processed into an electrode as described in Example I. An electrochemical cell was then similarly fabricated according to the same procedure as in Example I. Electrochemical testing of the cell was performed, including electrochemical impedance spectroscopy and five galvanostatic charge-discharge cycles at a charge rate of 1C and discharge rates of 0.2C, 1C, 5C, 10C, and 20C.

[0067] 6 shows a collection of discharge curves for the electrochemical cell of Example III at 1 C, 5 C, 10 C and 20 C. Unlike the cell of Example I, the cell of Example III only achieves 41% of its nominal capacity when discharged at 20 times the nominal rate.

[0068] Example IV:

[0069] Na 1.24 Mn 0.77 Fe 0.23 [Fe(CN)6] 0.88 (H2O) 2.57 and has a tap density of 0.83 g / cm 3 , specific surface area 4.69m 2 The TMCCC cathode material, having a ZnO content of 0.01% by mass and D10, D50, and D90 values ​​of 5.9 μm, 9 μm, and 13.9 μm / g, respectively, was processed into electrodes as described in Example I. Electrochemical cells were then fabricated following the same procedure as in Example I. Electrochemical impedance spectroscopy was then performed on these cells.

[0070] Example V:

[0071] Na 1.25 Mn 0.79 Fe 0.21 [Fe(CN)6] 0.88 (H2O) 3.53 and has a tap density of 0.83 g / cm 3 , specific surface area 4.71m 2The TMCCC cathode material, having a ZnO content of 1.0 μm / g and D10, D50, and D90 values ​​of 5.9 μm, 9 μm, and 13.5 μm, respectively, was processed into electrodes similar to the method described in Example I. Electrochemical cells were then fabricated similar to the procedure in Example I. Electrochemical impedance spectroscopy was then performed on these cells.

[0072] Example VI:

[0073] Na 1.24 Mn 0.78 Fe 0.22 [Fe(CN)6] 0.88 (H2O) 3.63 and has a tap density of 0.84 g / cm 3 , specific surface area 3.99m 2 The TMCCC cathode material, having a ZnO content of 1.0 μm / g and D10, D50, and D90 values ​​of 6.3 μm, 9.4 μm, and 13.4 μm, respectively, was processed into electrodes similar to the method described in Example I. Electrochemical cells were then fabricated similar to the procedure in Example I. Electrochemical impedance spectroscopy was then performed on these cells.

[0074] Example VII:

[0075] Na 1.17 Mn 0.75 Fe 0.25 [Fe(CN)6] 0.87 (H2O) 2.61 and has a tap density of 0.57 g / cm 3 , specific surface area 4.69m 2 The TMCCC cathode material, having a ZnO content of 1.0 μm / g and D10, D50, and D90 values ​​of 6.7 μm, 11.5 μm, and 17.4 μm, respectively, was processed into electrodes similar to the method described in Example I. Electrochemical cells were then fabricated following the same procedure as in Example I. Electrochemical impedance spectroscopy was then performed on these cells.

[0076] Example VIII:

[0077] Na 1.15 Mn 0.75Fe 0.25 [Fe(CN)6] 0.86 (H2O) 2.44 and has a tap density of 0.68 g / cm 3 , specific surface area 2.96m 2 The TMCCC cathode material, having a ZnO content of 1.0 μm / g and D10, D50, and D90 values ​​of 5.6 μm, 9 μm, and 13.5 μm, respectively, was processed into electrodes similar to the method described in Example I. Electrochemical cells were then fabricated following the same procedure as in Example I. Electrochemical impedance spectroscopy was then performed on these cells.

[0078] Example IX:

[0079] Na 1.22 Mn 0.77 Fe 0.23 [Fe(CN)6] 0.87 (H2O) 2.50 and has a tap density of 0.66 g / cm 3 , specific surface area 5.47m 2 The TMCCC cathode material, having a ZnO content of 1.0 μm / g and D10, D50, and D90 values ​​of 5.7 μm, 10.8 μm, and 17.2 μm, respectively, was processed into electrodes similar to the method described in Example I. Electrochemical cells were then fabricated similar to the procedure in Example I. Electrochemical impedance spectroscopy was then performed on these cells.

[0080] Table 1 summarizes a set of physical parameters of the TMCCCs in these examples, as well as the semicircular widths of the corresponding electrochemical cells. [Table 1]

[0081] Additional examples further highlight the importance of controlling the D10, D50, and D90 parameters of TMCCC to improve post-synthesis processing, such as producing TMCCC that can be processed into electrochemical cells with improved properties.

[0082] Example X:

[0083] K 0.63 Na 0.0045 Mn 0.72 Fe 0.28 [Fe(CN)6] 0.81 (H2O) 2.49 TMCCC cathode material with a composition of 0.01 μm, D10, D50, D90 of 4.9 μm, 7.0 μm, and 9.2 μm was mixed with an elastomeric adhesive binder and carbon black in an organic solvent blend to form a slurry. The slurry was deposited onto a carbon-coated aluminum foil current collector using a drawdown coater and dried at 60 °C for 35 minutes to evaporate the solvent. Electrodes were punched out of the coat using a die punch. Figure 7 shows the assembly of the subsequent electrodes made with the TMCCC of Example X with no obvious surface defects.

[0084] Example XI:

[0085] K 1.18 Mn 0.80 Fe 0.20 [Fe(CN)6] 0.86 (H2O) 5.93 and D10, D50, D90 of 1.1 μm, 3.6 μm, and 6.9 μm were processed into electrodes in a manner similar to Example X.

[0086] Figure 8 shows the resulting coating made using the TMCCC of Example XI. In contrast to the electrode seen in Figure 7, Figure 8 shows severe condensation on the coating obtained from the material of Example XI. It is believed that severe condensation may result from TMCCC having D10, D50, D90 outside the ranges specified herein as part of the preferred hierarchy. Such condensation prevents the TMCCC from being reliably converted into an electrochemical cell.

[0087] The proposed use of TMCCC is not limited by the choice of anode used when assembling the electrochemical cell. Possible anodes that can be paired with the TMCCC electrode include, but are not limited to, TMCCC electrodes such as Prussian Blue Analogue (PBA), carbon electrodes such as graphite, hard carbon, or activated carbon electrodes, antimony-based electrodes, tin-based electrodes, and silicon-based electrodes. The following examples support the ability of TMCCC to form a functional electrochemical cell regardless of the choice of anode.

[0088] Example XII:

[0089] The TMCCC cathode material described in Example I and the TMCCC described in Example IX were mixed in a ratio of 76:24. This TMCCC blend was then mixed overnight with an elastomeric adhesive binder and nanoparticle carbon black in an organic solvent blend to form a slurry. The ensuing slurry was then coated onto a carbon-coated aluminum foil using a slot die coater and then passed through a series of chamber ovens. This coat was then calendered (roll pressed) to further increase its density, vacuum dried, and finally punched into electrodes using a fitted metal press to form electrodes. The electrodes were then dried in a vacuum dryer to remove moisture in the electrodes. A Honbro Z stacker then fabricated an electrochemical cell by weaving the dried TMCCC electrode and PBA anode electrode with a porous membrane separator. An electrolyte containing bis(trifluoromethanesulfonyl)imide sodium (I) salt and acetonitrile solvent was then added to the cell, which was then sealed in a laminate pouch. The completed cell underwent a full discharge at 1 C followed by charge-discharge cycling at 1 C. Figure 9 shows the charge-discharge cycling at 1 C of the electrochemical cell prepared in Example XII, confirming that a functional electrochemical cell can be prepared by pairing a TMCCC cathode electrode with a PBA anode.

[0090] Example XIII:

[0091] TMCCC cathode material similar to that described in Example I was mixed with an elastomeric adhesive binder and nanoparticle carbon black in an organic solvent blend overnight to form a slurry. This slurry was deposited onto a carbon-coated aluminum foil current collector using a Frontier Coater and dried at 80°C for 35 minutes to evaporate the solvent. Subsequent coats were calendered (roll pressed) to further densify it, vacuum dried, and cut into electrodes for use in electrochemical cells. The TMCCC electrodes were paired with a hard carbon anode electrode and then assembled into an electrochemical cell containing a porous membrane separator and an electrolyte containing bis(trifluoromethanesulfonyl)imide sodium (I) salt and acetonitrile solvent. Prior to electrochemical testing, the cells were massaged and left to soak overnight to allow the electrolyte to seep through the pores. The cells were then subjected to charge-discharge cycles at a rate of C / 10. The cells were then subjected to galvanostatic cycling at C / 5. FIG. 10 shows the charge / discharge curves at C / 5 of Example XIII, demonstrating that a functional electrochemical cell can be made by pairing a TMCCC cathode with a hard carbon anode.

[0092] Example XIV:

[0093] Na 1.65 Mn 1.03 [Fe(CN)6] 0.92 (H2O) 1.96TMCCC cathode material with a composition of 0.01% by weight and D10, D50, D90 of 1.5 μm, 10.0 μm, 20.1 μm was mixed with an elastomeric adhesive binder and carbon black in an organic solvent blend to form a slurry. The slurry was deposited onto a carbon-coated aluminum foil current collector using a drawdown coater and dried at 60° C. for 35 minutes. The subsequent coat was calendered (roll pressed) to further densify it, vacuum dried, and cut into electrodes for use in electrochemical cells. The TMCCC electrode was paired with an activated carbon electrode and then assembled into an electrochemical cell containing a porous separator and an electrolyte containing ethylene carbonate and diethylene carbonate. Prior to electrochemical testing, the cell was vacuum sealed, massaged, and left to soak overnight to allow the electrolyte to seep through the pores. The cell was then subjected to charge-discharge cycling at a rate of C / 5. FIG. 12 shows a collection of charge / discharge curves at C / 5 of an electrochemical cell made with the material in Example XIV, where L x M y N z Ti a1 V a2 Cr a3 Mn a4 Fe a5 Co a6 Ni a7 Cu a8 Zinc a9 Ca a10 Mg a11 [R(CN)6] b (H2O) c We demonstrate that TMCCC in this form can be used to fabricate functional electrochemical cells.

[0094] The previous examples included compositions containing both iron (Fe) and manganese (Mn) on the nitrogen sites of the TMCCC material. Example XIV demonstrates that iron (Fe) is not required on the nitrogen sites.

[0095] While REF[2] investigates the role of particle size of TMCCC-containing cells on their electrochemical performance, this reference appears to focus on single crystalline particles of TMCCC's single chemical composition, KNi[Fe(CN)6], with a limited range of particle size, ranging from 0.038 μm to 0.38 μm. Embodiments of the present invention may relate to TMCCCs containing polycrystalline particles ranging from 6 to 20 μm. This size discrepancy indicates a difference in TMCCC technology, where REF[2] and other technologies can address nanoparticulate TMCCC, but some current embodiments of the present invention require TMCCCs with hierarchical structures. In other words, the TMCCCs currently discussed are composed of weak aggregates of strong aggregates that in turn are composed of individual crystals. Figure 11 shows, using SEM images, the hierarchical structure of the hierarchical TMCCCs of the present disclosure in contrast to the nanoparticulate TMCCCs described in REF[2]. As used herein, the term "strong aggregates" is defined as ellipsoidal clusters of interconnected TMCCC crystals. As used herein, the term "weak aggregates" is defined as clusters of stronger aggregates that have fused or otherwise combined.

[0096] For the purposes of presenting embodiments of the present invention, the above description of particle hierarchy addresses many implementations. There is a nuance that there may be multiple levels of hierarchy in the particle structure. In the simple case, the primary crystallites are stuck together into large particles that are very dense (microscope images may not show any pores and area measurements may only detect the outer surface area of ​​the particle). In other cases, the primary crystallites are stuck together very tightly into somewhat denser "sub-particles" that are then more loosely bonded together into even larger particles. In this case, imaging can visualize the pores between the sub-particles. Such particle hierarchy distributions and implementations are within the scope of the present invention.

[0097] 13 shows a typical electrochemical cell 1300. The cell 1300 includes a first electrode 1305 (e.g., a cathode electrode), a second electrode 1310 (e.g., an anode electrode), a liquid electrolyte 1315, a separator 1320, a first current collector 1325, and a second current collector 1330. One or both electrodes include a coordination compound, more specifically a transition metal cyanide coordination compound.

[0098] References:

[0099] The following references are cited herein, each of which is expressly incorporated herein by reference in its entirety for all purposes.

[0100] REF[1]-U.S. Patent No. 9,608,268-Alkali and alkaline-earth ion batteries with non-metal anode and hexacynometallate cathode,

[0101] REF[2]-Li et al., Li-ion and Na-ion insertion into size-controlled nickel hexacynoferrate nanoparticles, RSC Advances, 2014, 4, 24955-24961.

[0102] The above systems and methods are described in general terms to aid in understanding the details of the preferred embodiments of the present invention. Within the description herein, numerous specific details, such as examples of components and / or methods, are provided to provide a thorough understanding of the embodiments of the present invention. Some features and advantages of the present invention are realized in such a manner, and are not required in all cases. However, those skilled in the art will recognize that the embodiments of the present invention can be practiced without one or more of the specific details, or with other devices, systems, assemblies, methods, components, materials, and / or parts, etc. In other instances, well-known structures, materials, or operations are not specifically shown or described in detail to avoid obscuring aspects of the embodiments of the present invention.

[0103] References throughout this specification to "one embodiment," "an embodiment," or "a particular embodiment" mean that a particular feature, structure, or characteristic described in connection with that embodiment is included in at least one embodiment of the invention, but not necessarily in all embodiments. Thus, each appearance of the phrases "in one embodiment," "in an embodiment," or "in a particular embodiment" in various places throughout this specification does not necessarily refer to the same embodiment. Furthermore, the particular features, structures, or characteristics of any particular embodiment of the invention can be combined in any suitable manner with one or more other embodiments. It should be understood that other variations and modifications of the embodiments of the invention described and illustrated herein are possible in light of the teachings herein and are to be considered as part of the spirit and scope of the invention.

[0104] It will also be understood that one or more of the elements shown in the drawings / figures may be implemented in a more separate or integrated manner, or may even be removed or rendered inoperative in certain cases, as may be useful depending on the particular application.

[0105] Additionally, any signal arrows in the drawings / figures should be considered as illustrative only and not limiting unless otherwise noted. Combinations of components or steps may also be noted, and terminology may be expected but unclear as giving the ability to separate or combine.

[0106] The foregoing description of illustrated embodiments of the invention, including what is described in the Abstract, is not intended to be exhaustive or to limit the invention to the precise forms disclosed herein. Specific embodiments and examples of the invention have been described herein for illustrative purposes only, but various equivalent modifications are possible within the spirit and scope of the invention, as those skilled in the art will recognize and appreciate. As indicated, these modifications may be made to the invention in light of the foregoing description of illustrated embodiments of the invention and are intended to be within the spirit and scope of the invention.

[0107] Thus, although the invention has been described herein with reference to specific embodiments thereof, it will be understood that freedom of modification, various changes and substitutions are contemplated in the foregoing disclosure, and that in some instances, some features of the embodiments of the invention may be employed without the corresponding use of other features without departing from the scope and spirit of the invention as described. Accordingly, many modifications may be made to adapt a particular situation or material to the essential scope and spirit of the invention. The invention is not limited to the specific terms used in the following claims and / or to the particular embodiment disclosed as the best mode contemplated for carrying out the invention, but rather, it is intended that the invention include any and all embodiments and equivalents falling within the scope of the appended claims. The scope of the invention is therefore to be determined solely by the appended claims.

Claims

1. L x M y N z Ti a1 V a2 Cr a3 Mn a4 Fe a5 Co a6 Ni a7 Cu a8 Zinc a9 Ca a10 Mg a11 [R (CN) 6 ] b (H 2 O) c and A plurality of particles of said composition. A coordination complex comprising: the plurality of particles comprises a hierarchical structure, the hierarchical structure comprises a plurality of primary crystallites having a size D1, the plurality of primary crystallites being aggregated into a collection of agglomerates, each agglomerate having a size D2>D1; Each of L, M and N represents an alkali metal; R represents a metal cation optionally including one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ca, Mg, etc.; 0≦x≦2, 0≦y≦x, 0≦z≦x, 0<b≦1, 0<c, For each element of the set {a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11}, 0≦{a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11}≦1; At least one of {a1, a2, a3, a4, a6, a7, a8, a9, a10, a11} is >0; A coordination complex, wherein a4>0.

2. 2. The coordination complex of claim 1, wherein D1<1 μm.

3. 3. The coordination complex of claim 2, wherein D2 comprises a particle size distribution having a 50th percentile size >6 μm.

4. 4. The coordination complex of claim 3, wherein the particle size distribution D2 comprises a 10th percentile size greater than 1.5 μm.

5. 5. The coordination complex of claim 4, wherein the particle size distribution D2 comprises a 90th percentile size greater than 7.5 μm.

6. The composition has a density of >2 ml per gram 2 2. The coordination complex of claim 1 comprising a specific surface area of

7. The composition has a density of >2 ml per gram 2 The coordination complex of claim 5 comprising a specific surface area of

8. The composition is <0.9g / cm 3 2. The coordination complex of claim 1 comprising a tap density of

9. The composition is <0.9g / cm 3 6. The coordination complex of claim 5 comprising a tap density of

10. The composition is <0.9g / cm 3 8. The coordination complex of claim 7 comprising a tap density of

11. 2. The coordination complex of claim 1, wherein a5>0.

12. 2. The coordination complex of claim 1, wherein a5=0.

13. one or more conductive carbons; one or more polymer binders; A current collector; One or more TMCCCs 1. A conductive structure for an electrochemical cell comprising: At least one of the conductive carbons includes nanoparticle carbon; The current collector includes a metal foil, the metal foil comprises a surface coating comprising a carbon material; the polymer binder comprises a functionalized SEBS binder; The TMCCC comprising: L x M y N z Ti a1 V a2 Cr a3 Mn a4 Fe a5 Co a6 Ni a7 Cu a8 Zinc a9 Ca a10 Mg a11 [R (CN) 6 ] b (H 2 O) c and comprising a plurality of particles of said composition; the plurality of particles comprises a hierarchical structure; the hierarchical structure comprises a plurality of primary crystallites having a size D1, the plurality of primary crystallites being aggregated into a collection of weak aggregates, each weak aggregate having a size D2>D1; Each of L, M and N represents an alkali metal; R represents a metal cation optionally including one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ca, Mg, and the like; 0≦x≦2, 0≦y≦x, 0≦z≦x, 0<b≦1, 0<c, For each element of the set {a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11}, 0≦{a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11}≦1; At least one of {a1, a2, a3, a4, a6, a7, a8, a9, a10, a11} is >0; a4>0, The conductive structure, wherein 0.25 μm<D1<1 μm.

14. 14. The structure of claim 13, wherein a5>0.

15. 14. The structure of claim 13, wherein a5=0.

16. a cell stack having a liquid electrolyte, an anode electrode, a separator, and a cathode electrode; an electrochemical cell, the electrodes being in electrochemical communication with the liquid electrolyte, the liquid electrolyte comprising a polar organic solvent in combination with an alkali metal salt; the separator comprises a polymer membrane; the anode electrode comprises TMCCC; the anode electrode comprises conductive carbon; the cathode electrode comprises TMCCC; The TMCCC comprising: L x M y N z Ti a1 V a2 Cr a3 Mn a4 Fe a5 Co a6 Ni a7 Cu a8 Zinc a9 Ca a10 Mg a11 [R (CN) 6 ] b (H 2 O) c and further comprising a plurality of particles of said composition; the plurality of particles comprises a hierarchical structure, the hierarchical structure comprises a plurality of primary crystallites having a size D1, the plurality of primary crystallites being aggregated into a collection of agglomerates, each agglomerate having a size D2>D1; Each of L, M and N represents an alkali metal; R represents a metal cation optionally including one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ca, Mg, etc.; 0≦x≦2, 0≦y≦x, 0≦z≦x, 0<b≦1, 0<c, For each element of the set {a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11}, 0≦{a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11}≦1; At least one of {a1, a2, a3, a4, a6, a7, a8, a9, a10, a11} is >0; a4>0, An electrochemical cell, wherein 0.25 μm<D1<1 μm.

17. 17. The electrochemical cell of claim 16, wherein the cell stack includes one or more additional anodes, cathodes, or reference conductive structures, and combinations thereof.

18. 17. The electrochemical cell of claim 16, wherein the electrolyte comprises one or more nitriles.

19. 17. The electrochemical cell of claim 16, wherein the one or more nitriles are selected from the group consisting of acetonitrile and succinonitrile.

20. 17. The electrochemical cell of claim 16, wherein the liquid electrolyte comprises a combination of one or more cyclic carbonates and one or more linear carbonates.

21. 17. The electrochemical cell of claim 16, wherein the one or more cyclic carbonates are selected from the group consisting of ethylene carbonate and propylene carbonate, and the one or more linear carbonates are selected from the group consisting of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

22. 17. The electrochemical cell of claim 16, wherein the polymer membrane comprises a surface coating comprising nanoparticulate alumina and boehmite.

23. 17. The electrochemical cell of claim 16 configured as a hybrid capacitor with the anode electrode configured as a capacitive electrode.

24. 17. The electrochemical cell of claim 16, wherein the electrolyte comprises one or more nitriles, the one or more nitriles selected from the group consisting of acetonitrile and succinonitrile, the liquid electrolyte comprises a combination of one or more cyclic carbonates and one or more linear carbonates, the one or more cyclic carbonates selected from the group consisting of ethylene carbonate and propylene carbonate, the one or more linear carbonates selected from the group consisting of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, and the polymer membrane comprises a surface coating comprising nanoparticulate alumina and boehmite.

25. The cell of claim 16, wherein a5>0.

26. 17. The cell of claim 16, wherein a5=0.

27. 1. A method of manufacturing a conductive structure for an electrochemical cell, comprising the steps of: a) providing an electrochemically active material comprising agglomerated TMCCC; b) providing a conductive material; c) bonding the electrochemically active material to the conductive material to produce a hierarchical structure, the hierarchical structure comprising a plurality of primary crystallites having a size D1, the plurality of primary crystallites being aggregated into a collection of agglomerates, each agglomerate having a size D2>D1; A method comprising:

28. The agglomerated TMCCC comprises: L x M y N z Ti a1 V a2 Cr a3 Mn a4 Fe a5 Co a6 Ni a7 Cu a8 Zinc a9 Ca a10 Mg a11 [R (CN) 6 ] b (H 2 O) c and comprising a plurality of particles of said composition; the plurality of particles comprises a hierarchical structure, the hierarchical structure comprises a plurality of primary crystallites having a size D1, the plurality of primary crystallites being aggregated into a collection of agglomerates, each agglomerate having a size D2>D1; Each of L, M and N represents an alkali metal; R represents a metal cation optionally including one or more of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ca, Mg, etc.; 0≦x≦2, 0≦y≦x, 0≦z≦x, 0<b≦1, 0<c, For each element of the set {a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11}, 0≦{a1, a2, a3, a4, a5, a6, a7, a8, a9, a10, a11}≦1; At least one of {a1, a2, a3, a4, a6, a7, a8, a9, a10, a11} is >0; 28. The method of claim 27, wherein a4>0.

29. 29. The method of claim 28, wherein D1<1 μm.

30. 30. The method of claim 29, wherein D2 comprises a particle size distribution having a 50th percentile size > 6 μm.

31. 31. The method of claim 30, wherein the particle size distribution D2 comprises a 10th percentile size greater than 1.5 μm.

32. 32. The method of claim 31 , wherein the particle size distribution D2 comprises a 90th percentile size greater than 7.5 μm.

33. The composition has a density of >2 ml per gram 2 The method of claim 28, comprising a specific surface area of

34. The composition has a density of >2 ml per gram 2 The method of claim 32, comprising a specific surface area of

35. The composition is <0.9g / cm 3 The method of claim 28 comprising a tap density of

36. The composition is <0.9g / cm 3 The method of claim 32 comprising a tap density of

37. 29. The method of claim 28, wherein a5>0.

38. 29. The method of claim 28, wherein a5=0.